2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319969
|View full text |Cite
|
Sign up to set email alerts
|

A reliability assessment software using Kinect to complement the clinical evaluation of Parkinson's disease

Abstract: Parkinson's disease is characterized by alterations in the gait pattern that may increase the risk of falls. Variations in the gait pattern cannot be objectively measured in clinical examination, so it is necessary to adapt devices to measure objectively, valid and replicable changes in gait patterns that are part of the evolution of the disease and / or pharmacotherapy. In an interdisciplinary effort, we developed the "e-Motion Capture System" software, which is able to calculate motor (cadence, stride and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…They demonstrated a high accuracy of the Kinect sensor when measuring time and gross spatial characteristic movements relevant to PD and highly appropriate for distinguishing non-PD subjects from PD patients treated with deep brain stimulation. Likewise, the Kinect sensor has shown high validity regarding gait parameters when validated against a multiple-camera 3D motion capture system (41).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a high accuracy of the Kinect sensor when measuring time and gross spatial characteristic movements relevant to PD and highly appropriate for distinguishing non-PD subjects from PD patients treated with deep brain stimulation. Likewise, the Kinect sensor has shown high validity regarding gait parameters when validated against a multiple-camera 3D motion capture system (41).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy subjects, the stance time values were prolonged in the PD group. Previous studies on gait analysis in PD have also shown a higher stance time phase compared to controls, which they have associated with longer double limb support [19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Kinect is able to detect and track 20 different body joints (Figure 1(a)). Comparisons between the Kinect and benchmark references have shown a high agreement [19, 20]. Also, this device has been used in different research areas, like e-health [21, 22], security and surveillance [23–25], and UAV and robot vision [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Figura Por fim, a Figura 3. Da mesma forma, os conjuntos de dados resultantes do trabalho de Cunningham et al [41] avaliando a destreza da mão, Pastorino et al [42] que registram os dados de movimento do paciente para detectar a condição de medicação ON/OFF, a avaliação e o monitoramento da marcha propostos pelos autores Paredes et al [44], Pepa et al [50], e Patel et al [51]; o monitoramento da bradicinesia proposto por Eskofier et al [45], e os dados de avaliação da fala descritos pelos autores Dimauro et al [47]. Todos esses dados poderiam ser coletados do mesmo paciente, registrados no sistema (SIDABI), e poderiam ser comparados para uma melhor compreensão da doença, ou para monitorar a evolução do sintoma estudado, buscando proporcionar melhores condições de vida aos pacientes de uma maneira mais eficiente.…”
Section: Consulta De Dadosunclassified